High glucose and oxidative/nitrosative stress conditions induce apoptosis in retinal endothelial cells by a caspase-independent pathway - Leal, Ermelindo C. (2008)
http://www.sciencedirect.com/science/article/B6WFD-4V94X19-2/2/49680e499c2d31bd74eb7ad7fc99a8c2